Generation of Hydrogen in the Hydrolysis of NaBH4 Using Ir(0) Catalyst - Aksu1, Mecit (Asian Journal of Chemistry, 2014)
This study reports the results of kinetic of hydrogen generation from the catalytic hydrolysis of sodium borohydride. Iridium(0) particles catalyst was stabilized by diethylene glycol. Catalyst iridium was characterized by field emission scanning electron microscopy and energy dispersive X-ray spectroscopy. Hydrolysis of sodium borohydride was carried out both with and without stirring. Effect of stirring, sodium hydroxide concentration and sodium borohydride concentration on hydrogen volume and yield of hydrogen generation was investigated for optimization. It was found that rate of H2 generation decreased with increasing NaOH concentration while increased with increasing concentration of NaBH4. Stirring has positive effect on rate of hydrogen generation.